2001
DOI: 10.1007/s00330-001-1166-4
|View full text |Cite
|
Sign up to set email alerts
|

Chest imaging with flat-panel detector at low and standard doses: comparison with storage phosphor technology in normal patients

Abstract: The purpose of this study was to evaluate the performance of standard-dose and low-dose cesium iodide (CsI)-doted amorphous silicon (a-Si) flat-panel detector technology (FDT) as compared with storage-phosphor technology (SPT) in the depiction of relevant anatomical structures in chest radiography. In 75 patients referred for thoracic CT, digital chest radiographs were randomly obtained with either SPT at a standard dose (speed class S400, n=25), standard-dose FDT (S400, n=25) or FDT at a low dose (S800, n=25)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 21 publications
0
14
1
2
Order By: Relevance
“…In CR, image quality is deteriorated by internally generated noise in these systems, i.e., luminescence and granularity noise [1,2]. Superior image quality for CsI-FPD systems compared with GOS-FPD and CR could have been expected and has been reported in a number of studies [24,[28][29][30]. However, in the present study, the effective dose found for the CsI-FPD systems was at least a factor 2 lower than with the other systems.…”
Section: Discussioncontrasting
confidence: 77%
“…In CR, image quality is deteriorated by internally generated noise in these systems, i.e., luminescence and granularity noise [1,2]. Superior image quality for CsI-FPD systems compared with GOS-FPD and CR could have been expected and has been reported in a number of studies [24,[28][29][30]. However, in the present study, the effective dose found for the CsI-FPD systems was at least a factor 2 lower than with the other systems.…”
Section: Discussioncontrasting
confidence: 77%
“…To summarize the results of experimental and skeleton studies, FD at a simulated speed of 800, resulting in a dose reduction of 50%, is equivalent to SFR and SPR at a speed of 400 in terms of image quality criteria [9-11, 13-17, 22-24]. During routine chest radiography a dose reduction of 50% seemed to be possible [25,27]. Strotzer et al [26] performed a study with 30% dose reduction and the results showed no differences in image quality between FD at a simulated speed of 400 and 560, thus a dose reduction of 30% is possible without loss in diagnostic reliability.…”
Section: Resultsmentioning
confidence: 99%
“…Herrmann et al [27] evaluated the depiction of relevant anatomical structures in chest radiography using FD at simulated speeds of 400 and 800 and SFR at a speed of 400. In 75 patients referred for thoracic CT, digital chest radiographs were randomly obtained with either SPR or FD at a simulated speed of 400 or 800.…”
Section: Dose Reduction In Clinical Chest Radiographymentioning
confidence: 99%
“…The intrinsic superiority of detector-based radiography over film-screen and computed radiography also improved the image quality of DE techniques in direct comparison [14,15,16,17,18,19,20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%